Attitudes of tourism consumers towards the use of VR in the tourism industry and behavioural intentions to use this approach under the influence of COVID-19 - Zhang, Ya-Man (2022)
As the COVID-19 pandemic spreads worldwide, tourism has become one of the most affected sectors. In order to adapt to the pandemic and recover the tourism industry, VR technology is increasingly being used. As one of the most critical subjects in the tourism industry, the attitudes and perceptions of tourism consumers towards VR tourism in the current COVID-19 context have received increasing attention. However, previous research has typically focused on using the TAM framework based on quantitative studies. This study explores tourism consumers' attitudes towards using VR technology in tourism and their behavioural intentions to use this approach under the influence of COVID-19. Based on an inductive qualitative research approach, the researcher conducts semi-structured interviews with 16 participants and then analyses and discusses the final interview results using a thematic analysis approach combined with the TAM and PADM theoretical frameworks. The study shows that under the influence of COVID-19, travel consumers demonstrate a positive attitude to try using VR tourism. At the same time, VR tourism during an epidemic is both a risk-averse measure and an acceptance of new technology. In addition, travel consumers also shows behavioural intentions to recommend and re-experience. This study extends the qualitative research related to VR tourism and provides implications for the current study of VR tourism consumer behaviour in the context of COVID-19.